2001
DOI: 10.1590/s0100-879x2001000700007
|View full text |Cite
|
Sign up to set email alerts
|

HHV-8 infection in patients with AIDS-related Kaposi's sarcoma in Brazil

Abstract: The aims of the present study were to determine the prevalence of human herpesvirus type 8 (HHV-8) in HIV-positive Brazilian patients with (HIV+/KS+) and without Kaposis sarcoma (HIV+/KS-) using PCR and immunofluorescence assays, to assess its association with KS disease, to evaluate the performance of these tests in detecting HHV-8 infection, and to investigate the association between anti-HHV-8 antibody titers, CD4 counts and staging of KS disease. Blood samples from 66 patients, 39 HIV+/KS+ and 27 HIV+/KS-,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 25 publications
3
20
0
1
Order By: Relevance
“…Several studies conducted among healthy blood donor samples using real-time PCR showed no detection of HHV-8 viremia or a very low positivity of 1% [14,15]. Among Brazilian HIV-1-infected individuals HHV-8 viremia was seen in 74.3% of KS-positive patients and in 3.7% of KS-negative patients [16] and a report from Europe showed 12.6% of HIV-infected individuals to have HHV-8 DNA in their peripheral blood mononuclear cells [17]. The HHV-8 viremia reported prior to HAART was very high [3].…”
Section: Tablementioning
confidence: 99%
“…Several studies conducted among healthy blood donor samples using real-time PCR showed no detection of HHV-8 viremia or a very low positivity of 1% [14,15]. Among Brazilian HIV-1-infected individuals HHV-8 viremia was seen in 74.3% of KS-positive patients and in 3.7% of KS-negative patients [16] and a report from Europe showed 12.6% of HIV-infected individuals to have HHV-8 DNA in their peripheral blood mononuclear cells [17]. The HHV-8 viremia reported prior to HAART was very high [3].…”
Section: Tablementioning
confidence: 99%
“…In 2001 Keller et al 31 reported the seroprevalence of HHV-8 on HIV-positive patients. Using PCR, 74.4% (29/39) of the KS-positive patients and 3.7% (1/27) of the KS-negative patients were positive for the KS330 sequence.…”
Section: Brazilmentioning
confidence: 99%
“…Reports from Brazil and Cuba (Kouri V, 2004) showed that HHV-8 seroprevalence in patients with AIDS-associated Kaposi's sarcoma to be 79.5% and 77.8% respectively (Keller R, 2001;Kouri V, 2004). This rate was lower than those reported in Tanzania (Wamburu G, 2006), Central African Republic (Duprez R, 2003) and Zambia (He J, 1998) were rates 96.4%, 94% and 92.3% respectively recorded in AIDS-associated Kaposi's sarcoma.…”
Section: Discussionmentioning
confidence: 99%